BIM-based structural optimization for reinforced concrete floors using evolutionary algorithms - Sherif, Mohamed Ayman (AUC Knowledge Fountain, 2020)
Achieving the optimum design is to sustain the architectural function with minimum construction cost. Optimizing the design requires the architect to prepare several design alternatives with different space utilizations approaches without compromising the architectural requirements or the function of the building. For each design alternative, the structural engineer is required to study and validate the design with various alternatives of structural systems to achieve a safe, efficient, and constructible design. Due to the dynamic nature of this process, a building’s floor plan could have numerous combinations of alternatives that satisfy the architectural and functional requirements that need to be investigated to achieve the optimum cost. The literature has discussed various optimization approaches between the integration of architectural and the structural aspects during the design phases of projects. However, defining the possible integration between architectural and structural limits to reach an optimized design that fulfills the design functionality and is cost efficient was not much covered. This study presents a digital framework that integrates the architectural and structural design aspects to reach the optimum utilization between the functionality of the architectural design and savings in the structural design using BIM. A model was developed that maps elements onto a universal grid system where architects define the functionality limits such as, overall floor dimension, the number of spaces in the floor, the function of each space, the relative proximity of spaces and the acceptable dimension limits of such spaces. A built-in optimization engine using evolutionary algorithms to find the optimal structural design of the building that fulfills safety, constructability and with minimum use of building materials was also included in the model. The study covers three structural systems: the reinforced concrete solid slabs, flat slabs, and beams systems and is applied for rectilinear architectural spaces. The framework was tested and validated with a number of case studies. Results show that the model was able to produce cost savings from 5-15 % of the structural elements cost without compromising the defined space requirements.